Testing for memory in the Filipino elderly - Orteza, Grace O. (Philippine Journal of Psychology, 1999)
The rapidly aging population brings to fore health problems related to the elderly, one of the most feared of which is dementia of the Alzheimer's type (AD). Memory decline is the earliest presenting symptom of AD but must be differentiated from that which accompany normal aging, depression, substance abuse and other cognitive functions which are also common in the elderly. Furthermore, memory complaints increase with age and is independent of memory test performance. Different approaches and tools in memory assessment and their corresponding limitations for use among the Filipino elderly were reviewed. One of the most promising memory test is the Fuld Object Memory Evaluation Test (FOMET). A cross-sectional correlational study of 100 healthy adults with age ranging from 30 to 94 was conducted. It was found that FOMET measures were significantly correlated with age, years of education, and gender. Normal values for Filipino adults and elderly in the different FOMET measures, taking these three factors into consideration were presented. Recommendations for use of FOMET in memory testing of Filipino elderly were given.